PERAN INTEGRASI ETIKA KERJA ISLAM DALAM INTELLECTUAL CAPITAL UNTUK PENINGKATAN KINERJA UMKM - Dista Amalia Arifah; Abdul Hakim; Norazamina Mohamed (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Companies with excellent Intellectual Capital can be more competitive in the current business era if the companies are well managed. It is also applicable for Small and Medium Enterprises (SMEs). Islamic work ethics integration toward Intellectual Capital is expected to optimize the company performance further. This study aimed to explore and discuss the effect of Islamic work ethics integration in Intellectual Capital, consisting of human capital, structural capital, organizational capital, spiritual capital, and technological capital, toward SME performance improvement. The populations of this study were SMEs in Central Java. This study used purposive sampling as the sampling technique. Based on the data processing results, it obtained 300 sample data. The results showed that human capital does not affect SMEs' performance. Thus the hypotheses were rejected. The existing SMEs do not explore Intellectual Capital as a competitive advantage. As a result, the integration of Islamic work ethics in human capital does not improve performance. On the other hand, structural capital, organizational capital, spiritual capital, and technological capital impact SMEs' performance, so four hypotheses were accepted.